The transformed function is g(x) = -7
(-x) +2
The given base function is
f(x) =
(x)
Then we have to find the transformed function.
First of all, the graph of the base function f(x) =
(x) is vertically stretched by a factor of 7, then the newly transformed function becomes y = 7
(x)
Then the graph of y = 7
(x) is reflected over the x-axis, then the newly transformed function becomes y = -7log6(x)
Then the graph of y = -7
(x) is reflected over the y-axis, then the newly transformed function becomes y = -7
(-x)
And finally, the graph of y=7log6(-x) is vertically shifted up by 2 units, then the newly transformed function becomes
y = -7
(-x) +2
which is the required equation for the transformed function.